Analisis Peserta Online Test dengan Pembentukan Cluster dengan Algoritma K-Means dan Analisis Tabulasi - Kevin Chandra Gunawan (Jurnal Titra, 2020)
PT XYZ is one of the leading tobacco industries in Indonesia. PT XYZ manages more than 25,000 permanent employees both at the center and at subsidiaries. The company management has an international internship program to find quality human resources from an early age and as an employer branding container. The internship program is promoted to all universities in Indonesia with an initial selection stage using an online test. The company wants to know the grouping formed based on the first stage test data, namely the Situational Judgment Test (SJT) and Numerical. Grouping is done by using k-means clustering. Cluster results are used to classify the origin of student university. The relationship between the university and the cluster formed will be tested using tabulation and chi-square analysis. The results of grouping there are 4 clusters, there are clusters with both values having a high average. Another cluster with both low average values and the other with a combination of the two. The grouping shows that there are 4 universities that have a greater percentage than others in cluster 2 which have high average scores. There are 4 universities included in cluster 1 or groups with both low test scores.